PENGARUH TEKNIK BIBLIOTERAPI TERHADAP PERENCANAAN KARIR SISWA KELAS XI DI SMA NEGERI 1 TARAKAN TAHUN PELAJARAN 2018/2019 - Apriliana, Tiya; Aliyah, Urotul (Jurnal Bimbingan dan Konseling Borneo, 2019)
This research aims to determine the effect of bibliotherapy techniques on career planning of students in SMA Negeri 1 Tarakan. This research used quantitative research design through a quasi-experimental approach. The independent variable was bibliotherapy technique and the dependent variabel was the students? career planning. The population in this research were 216 students and used purposive sampling of 20 students at SMA Negeri 1 Tarakan as the technique of sampling. While for the instrument, this research used student career planning scale with the attitude measurement scale. In this research, descriptive statiscal analysis and inferensial were used as the data analysis.            Based on the results of data analysis and discussion of research results, it can be concluded that the career planning of class XI students at Tarakan 1 Public High School 2018/2019 Academic Year before being treated (pretest) the average score of 105.90 which means the average student has a plan medium career. After being given treatment (posttest) the results of the average score of 124.10, which means that most of the students have experienced an improvement in their career planning. This is reinforced by the results of the analysis shows the value of significance level of 0.000 which means smaller than the significance level of 5%. So it can be concluded that there is an influence of bibliotherapy techniques on the career planning of class XI students at SMA Negeri 1 Tarakan in the 2018/2019 school year.  Keywords: Bibliotherapy Technique, Student Career Planning